BIOMETRIC ATTENDANCE MONITORING SYSTEM OF CAGAYAN STATE UNIVERSITY – LASAM CAMPUS, PHILIPPINES - Maggay, Jake G. (International Journal of Research -GRANTHAALAYAH, 2017)
The study aimed to develop a fully customized Biometric Attendance Monitoring System (BAMS) of Cagayan State University – Lasam Campus, Philippines (CSU - Lasam) using biometric fingerprint reader to facilitate the monitoring of employees’ attendance. This study followed the framework of Design Science Research for Information Systems, thus, the researcher identified the problems and issues encountered in the monitoring of attendance, defined the objectives of the study, designed and developed the system, deployed and tested, and presented the result of the study. A combination of Visual Basic 6.0 as the programming language and MS Access as the Database Management Systems were used in the development of the system.Thus, the overall functionality of the BAMS enables the users to enter data, change and manipulate the data, get information, and store the data and the information. Username and password is no longer needed since all transactions use unique fingerprint to validate users. Furthermore, the BAMS greatly contributes in giving employees’ ease and improving work values. Likewise, the BAMS is essential in achieving good governance because it helps track day-to-day attendance of the employees.